The Dynamics of Social Communication among Muslims in Indonesia from the Perspective of Libraries and Sociology - Wahyudi Wahyudi; Andra Nurhaliza; Yusrotul Amalia; Ripo Nurapil Wicaksono; Marissakh Diana Martabillah (Bulletin of Indonesian Islamic Studies, 2025)
As access to religious information through digital media and libraries in Indonesia becomes more widespread, patterns of social communication among Muslims are facing new challenges in the form of the spread of uncurated information, differences in interpretation, and the potential for polarization. This situation highlights the need for an in-depth study of the dynamics of social communication among Muslims amid rapid social change. This study uses data collection techniques through in-depth searches of relevant library sources. Data was obtained from books on Islamic communication, library science literature, scientific journal articles, sociological theories, digital library repositories, religious institution reports, and research on da'wah media. All sources were selected systematically based on thematic relevance and scientific credibility. The results of the study show that the dynamics of social communication among Muslims in Indonesia are greatly influenced by library literacy and the flow of digital information. Expanded access to knowledge shapes the way people interact and understand religious teachings, while sociological perspectives explain how digital culture encourages more participatory communication patterns. This research provides a conceptual basis for the development of more adaptive religious information literacy, enabling the community to critically sort through information.